Perfil epidemiológico dos casos de tuberculose resistente em hospital especializado - Zanoti, Márcia Diana Umebayashi (2010)
Tuberculosis (TB) remains a major challenge to the health sector, both by the high incidence of the disease and the emergence of resistant strains, making it a priority on the global agenda of Health. The aim of this study was to characterize the epidemiological profile of TB cases resistant at the Hospital Estadual Nestor Goulart Reis in Américo Brasiliense - SP. This is a retrospective, exploratory and descriptive study, which analyzed 55 adult patients of both sexes, with positive culture results for Mycobacterium tuberculosis that presented any antibiotic drug resistance and who were tested at the hospital between January 2005 to December 2008, comprising 10.9% of inpatients. All of them had pulmonary tuberculosis disease, 70.9% were men, at admission 69.1% were unemployed and 81.8% had one hospitalization. Among the associated comorbidities, alcoholism emerged with 43.6% and AIDS with 10.2%, over 70% were referred from primary care and specialty clinic; 32.7% were resistant to at least one drug and 54.5% TB were multiple drugs resistant. The treatment most used was the Scheme 1 in 31% of patients and Scheme 1R in 18,2%. It was observed fragility in the adequacy of the therapeutic scheme with the sensibility test, beyond the average time of 65 days to its return. Regarding the closure of cases, 23.6% were successfully cured and 12.7% died. It is concluded that the situation of TB drug-resistant in the study area deserves special attention considering that the cure rates are lower than recommended levels. It is suggested that the process of local work must be reassessed, particularly the flow of biological material, as well as a guarantee that such results subsidize the institution of drug therapy.